Self-Reported Food Insecurity in Africa During the Food Price Crisis - Marijke Verpoorten; Abhimanyu Arora; Johan F. M. Swinnen (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2012)
This article analyzes data on self-reported food insecurity of more than 50,000 individuals in 18 Sub-Saharan African countries over the period 2005 to 2008, when global food prices increased dramatically. The average level of self-reported food insecurity was high but remarkably stable, at about 54%. However, this average hides large heterogeneity, both within countries and across countries. In eight of the sample countries, self-reported food security improved, while it worsened in the ten other countries. Our results suggest that heterogeneous effects in self-reported food security are consistent with economic predictions, as they are correlated with net food consumption (both at the household and country level) and economic growth. Specifically, self-reported food security improved on average in rural households, while it worsened in urban households. Improvements in food security were positively correlated with net food exports and Gdp per capita growth. We estimate that over the period 2005-2008 between 5 and 12 million people in the 18 SSA countries became more food secure. While the self-reported indicator used in this paper requires further study and one should carefully interpret the results, our findings suggest the need for a critical evaluation of the currently used data in the public debate on the food price crisis, which makes mention of hundreds of millions of additional food insecure.
Keywords: Q18; I32; O55; 330; Food policy; food insecurity measurement; Sub-Saharan Africa; food crisis